The Relationship between Stunting and Body Resistance to Infection in Children: A Literature Review - Candra, Aisyah; Handini, Laksmi Suci (Journal of Diverse Medical Research: Medicosphere, 2025)
Background: Stunting is a chronic nutritional problem due to malnutrition, especially during the first 1,000 days of life. In addition to affecting physical growth, stunting also affects children's cognitive development and immune system. Stunted children have a higher risk of recurrent infections such as respiratory infections and diarrhea, because their immune systems are not yet optimally developed. In Indonesia, the prevalence of stunting is still quite high and is one of the main health problems, caused by prolonged malnutrition that weakens the function of the child's immune system. Objective: To determine the relationship between stunting and resistance to infection in children, as well as the role of proper nutrition in improving health and endurance. Methods: A literature review covering various scientific sources from 2019-2024 through the Google Scholar, PubMed, and Science Direct databases with the keywords "stunting," "immunity," "infection," and "children." Secondary data on the prevalence of stunting and infection are used to show the relationship between these two factors. Results and Discussion: Stunted children are more susceptible to infection because their immune systems are not yet optimal due to a lack of essential nutrients such as protein, zinc, and vitamins. Research shows that an unbalanced diet and zinc deficiency can weaken the immune response, making children more likely to experience respiratory infections and diarrhea. Repeated infections worsen their nutritional status, creating a cycle of malnutrition and infection that is difficult to break. Conclusion: Stunting is closely related to low body resistance to infection. Children who experience stunting have a higher risk of recurrent infections due to a less than optimal immune system. Appropriate nutritional intake, such as protein, zinc, and vitamins, plays an important role in increasing immunity and overcoming stunting.